Preemption in capacity and price determination: A study of endogenous timing of decisions for homogeneous markets - Sandra Güth; Werner Güth (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
The theory of industrial organization has experienced an impressive boom by using the methods of (non-cooperative) game theory. The conclusions depend, however. crucially on subtle details of the market decision processes about which there exist no or little empirical information. Studies of endogenous timing could help since they derive the time structure of decision making instead of assuming it as exogenously given. In our study we consider a homogeneous market where, like in the model of Kreps and Scheinkman (1983), sellers determine sales capacities before prices. To avoid rationing sellers must serve customers, but at higher costs when demand exceeds capacity. Our model allows for preemption in capacity as well as in price determination. Since preemption means to decide before the random choice of cost parameters reflecting the stochastic nature of (excess) capacity costs, preemptive commitments are no obviously better timing dispositions.
urn:nbn:de:kobv:11-10060718
Keywords: 330